2016
DOI: 10.18632/oncotarget.11410
|View full text |Cite
|
Sign up to set email alerts
|

Induction of exportin-5 expression during melanoma development supports the cellular behavior of human malignant melanoma cells

Abstract: Regulation of gene expression via microRNAs is known to promote the development of many types of cancer. In melanoma, miRNAs are globally up-regulated, and alterations of miRNA-processing enzymes have already been identified. However, mis-regulation of miRNA transport has not been analyzed in melanoma yet. We hypothesized that alterations in miRNA transport disrupt miRNA processing. Therefore, we investigated whether the pre-miRNA transporter Exportin-5 (XPO5) was involved in altered miRNA maturation and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Recent studies have shown that Exportin-5 plays an important role in tumorigenesis. A study by Ott et al [ 14 ] found that a high abundance of exportin-5 in the melanoma leads to enhanced survival, proliferation and metastasis and thereby supports the aggressiveness of the cancer [ 14 ]. Studies have reported that endogenous IL-18 can affect hepatic metastasis by upregulating melanoma cell adhesion to HSE cells and tumor growth, implicating a possible antimetastatic benefit of neutralizing IL-18.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that Exportin-5 plays an important role in tumorigenesis. A study by Ott et al [ 14 ] found that a high abundance of exportin-5 in the melanoma leads to enhanced survival, proliferation and metastasis and thereby supports the aggressiveness of the cancer [ 14 ]. Studies have reported that endogenous IL-18 can affect hepatic metastasis by upregulating melanoma cell adhesion to HSE cells and tumor growth, implicating a possible antimetastatic benefit of neutralizing IL-18.…”
Section: Resultsmentioning
confidence: 99%
“…MicroRNAs (miRs) are posttranscriptional regulators of gene expression and crucial mediators of tumorigenicity in melanoma (Bosserhoff, ; Dietrich & Bosserhoff, ; Kappelmann, Kuphal, Meister, Vardimon, & Bosserhoff, ; Mione & Bosserhoff, ; Ott, Linck, Kremmer, Meister, & Bosserhoff, ). For example, miR‐125b was shown by our group to control melanoma progression by direct regulation of c‐Jun (Kappelmann et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Small molecule targeting of epigenetic enzymes, for example, histone deacetylases (HDACs) or specific transcription factors (TF) can reactivate the expression of tumor-suppressive miRNAs [196,258,266,270]. Drosha expression could be induced or XPO5 expression could be inhibited by siRNA leading to induction or repression of tumorigenic miRNAs [271,272]. To inhibit binding of the negative regulator LIN28 to the tumor-suppressive miRNA let-7, short, loop-targeting "looptomiRs" can be used [273].…”
Section: Genetic Alterations Transcriptional Regulation and Mirna-edmentioning
confidence: 99%
“…We identified XPO5 as significantly overexpressed in melanoma compared to normal human epidermal melanocytes (NHEM), contributing to enhanced survival, proliferation and metastasis of melanoma cells [272]. The enhanced XPO5 expression is partly due to constitutively active MEK/ERK signaling in melanoma and partly due to increased mRNA stability because of a single nucleotide polymorphism (SNP; rs11077) in the miR-617 binding site [272]. In HCC, the A/A genotype of the same SNP is associated with worse survival of HCC patients [296].…”
Section: Protein Regulators Of Microrna Expression and Functionmentioning
confidence: 99%
See 1 more Smart Citation